Use and perception of information sources on COVID-19 measures by citizens of Belgium - van Loenhout, Joris Adriaan Frank; Aujoulat, Isabelle; Van den Broucke, Stephan (Frontiers in Communication, 2022)
Background: The effectiveness of adherence to COVID-19 infection prevention and control (IPC) measures depends on effective risk communication. This study assessed use and perception of COVID-19 information sources and channels in Belgium, and the relationship with adherence to measures Methods: Data were collected through an online questionnaire among a sample of 2008 respondents, representative for citizens of Belgium in terms of gender, age, socio-economic status and region. Potential information sources named in the questionnaire were politicians, experts, journalists and close contacts. Results: Overall, experts contributed most to informing people on COVID-19 measures, and their information was considered clearest and most trustworthy, while politicians scored lowest for information clarity. All information channels were used by large proportions of respondents, namely television 80.2%, (online) newspapers 56.5%, radio 35.7% and social media 27.7%. Factors that contributed significantly to adherence in a multivariate model included use and perception of information from experts, which had a positive association, and relying on social media as an information channel, for which the relationship was negative. Conclusions: It is important to achieve clear and trustworthy risk communication, as this contributes to overall adherence to IPC measures on COVID-19. Furthermore, attention should be given to the fact that for people who rely on social media as an information channel, their adherence can be adversely affected.